Solid-liquid-gas synergistic discharge relay type lithium battery and preparation method thereof
Patent Information
- Application Number
- CN202311755339.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-19
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-12-19
AI Technical Summary
但是未专门为接力体系进行设计,因而未考虑电极对于六氟化硫气体的透过性,不具有较高的比表面积,因而难以使得六氟化硫充分反应
[0020] 1. This invention selects nitrogen-doped mesoporous carbon with low density, high electronic and ionic conductivity, and high specific surface area as the conductive agent for the electrode. Simultaneously, the mass ratio of nitrogen-doped mesoporous carbon is significantly increased, thus greatly enhancing the specific surface area and electron and ion transport rates of the relay battery's positive electrode. Furthermore, the use of fluorinated carbon materials with high specific surface area effectively regulates the structure of the carbon in the reaction products, providing sufficient active sites for the subsequent reaction of sulfur hexafluoride and the relay electrolyte. At the same time, the pyridine nitrogen and pyrrole nitrogen functional groups in the conductive agent have strong nucleophilicity, thus reducing the bond energy of the sulfur-fluorine bond and increasing the gas adsorption capacity through an inductive effect, thereby increasing the discharge voltage of sulfur hexafluoride and further improving the discharge specific energy of the relay battery.
Smart Images

Figure CN117673388B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium battery technology, specifically relating to a relay-type lithium battery with solid-liquid-gas synergistic discharge and its preparation method. Background Technology
[0002] Lithium metal primary batteries have been widely used due to their high specific energy and relatively flat discharge voltage plateau caused by their reaction mechanism based on conversion reactions. Among them, fluorinated carbon materials have a discharge specific energy as high as 2200 Wh / kg. However, with the development of modern technology, there are higher demands on the specific energy of lithium fluorinated carbon batteries, and increasing the proportion of active materials in the battery is an effective method.
[0003] Existing technology CN109659515A describes a method for preparing Ag@C modified fluorinated carbon electrode materials. This method primarily employs a chemical reduction approach to reduce Ag compounds to Ag while simultaneously reducing some fluorinated carbon to carbon, thereby improving the conductivity of the fluorinated carbon material and effectively enhancing the electrode's rate performance. However, it is not specifically designed for a relay system and therefore does not consider the electrode's permeability to sulfur hexafluoride gas, resulting in a low specific surface area and making it difficult for sulfur hexafluoride to react fully.
[0004] The discharge products of lithium fluoride carbon materials are lithium fluoride and carbon. The carbon material generated has a high specific surface area and certain conductivity, so it can be used as a reaction medium for gas and active electrolyte, thereby realizing the relay discharge reaction of the battery. Summary of the Invention
[0005] To address the problems existing in the prior art, this invention provides a relay lithium battery with solid-liquid-gas synergistic discharge and its preparation method. The solid-liquid-gas synergistic discharge lithium-carbon-sulfur hexafluoride-active electrolyte relay lithium battery is prepared by constructing a highly conductive three-dimensional fluorinated carbon electrode and a multifunctional electrolyte.
[0006] This invention is achieved through a method for preparing a relay-type lithium battery with solid-liquid-gas synergistic discharge, comprising the following steps:
[0007] Step 1: Add the dry powders of fluorinated carbon, nitrogen-doped mesoporous carbon, and sodium carboxymethyl cellulose (CMC) to the ball mill jar in sequence, wherein the mass percentage of CMC is 2% and the mass percentage of nitrogen-doped mesoporous carbon is not less than 15%, and mix the dry powders evenly using a ball mill.
[0008] Step 2: Add distilled water to the uniform dry powder obtained in Step 1 to adjust the solid content of the slurry to 15%-25%, and continue to mix the slurry using a ball mill; the percentages are by mass.
[0009] Step 3: Add a water-based binder to the slurry obtained in Step 2. The binder accounts for 4% of the mass of the slurry. Continue to mix the slurry using a ball mill.
[0010] Step 4: The slurry obtained in Step 3 is evenly coated onto the ultrathin foam metal and dried at 100-150℃ for 10-12 hours under -80kPa to obtain the positive electrode sheet of the relay battery.
[0011] Step 5: Assemble the positive electrode, lithium metal and electrolyte obtained in Step 4 into a relay battery.
[0012] In step one, the fluorinated carbon used has a fluorine-to-carbon ratio not exceeding 1.3 and a specific surface area greater than 50 m². 2 / g; nitrogen content of nitrogen-doped mesoporous carbon ≥0.2%, percentage is by mass, specific surface area ≥20m² 2 / g, the ball mill speed is 250-350r / min, and the ball milling time is 1-1.5h.
[0013] In step two, the ball mill rotates at 350-450 r / min, and the milling time is 10-12 h, resulting in a uniform fluid mixture.
[0014] In step three, the water-based binder is one of polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), and polyacrylic acid (PAA), the ball mill speed is 250-270 r / min, and the ball milling time is 10-15 min.
[0015] In step four, the ultrathin foam metal is one of foamed nickel, foamed aluminum, and foamed nickel-molybdenum.
[0016] In step five, the electrolyte is LiNO3-DMAC / FEC, the concentration of LiNO3 is 0.8-2M, and the volume ratio of FEC does not exceed 6%.
[0017] In step one, the fluorinated carbon used has a fluorine-to-carbon ratio not exceeding 1.3 and a specific surface area greater than 50 m². 2 / g; nitrogen content of nitrogen-doped mesoporous carbon ≥0.2%, percentage is by mass, specific surface area ≥20m² 2 / g, the ball mill speed is 250-350 r / min, and the ball milling time is 1-1.5 h; in step two, the ball mill speed is 350-450 r / min, and the ball milling time is 10-12 h, and the final mixture is a uniform fluid; in step three, the aqueous binder is one of polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), and polyacrylic acid (PAA), and the ball mill speed is 250-270 r / min, and the ball milling time is 10-15 min; in step four, the ultrathin foam metal is one of foamed nickel, foamed aluminum, and foamed nickel-molybdenum; in step five, the electrolyte is LiNO3-DMAC / FEC, the concentration of LiNO3 is 0.8-2 M, and the volume ratio of FEC does not exceed 6%.
[0018] The above-described preparation method yields a relay-type lithium battery with solid-liquid-gas synergistic discharge.
[0019] The advantages and technical effects of this invention are as follows:
[0020] 1. This invention selects nitrogen-doped mesoporous carbon with low density, high electronic and ionic conductivity, and high specific surface area as the conductive agent for the electrode. Simultaneously, the mass ratio of nitrogen-doped mesoporous carbon is significantly increased, thus greatly enhancing the specific surface area and electron and ion transport rates of the relay battery's positive electrode. Furthermore, the use of fluorinated carbon materials with high specific surface area effectively regulates the structure of the carbon in the reaction products, providing sufficient active sites for the subsequent reaction of sulfur hexafluoride and the relay electrolyte. At the same time, the pyridine nitrogen and pyrrole nitrogen functional groups in the conductive agent have strong nucleophilicity, thus reducing the bond energy of the sulfur-fluorine bond and increasing the gas adsorption capacity through an inductive effect, thereby increasing the discharge voltage of sulfur hexafluoride and further improving the discharge specific energy of the relay battery.
[0021] 2. The use of water-based binders in this invention greatly reduces the environmental requirements of the slurry, while avoiding the damage to carbon-fluorine half-ionic bonds caused by NMP solvent in oil-based systems during homogenization. The operation steps are simple, the equipment used is simple, and it is easy to prepare.
[0022] 3. By using ultra-thin foam metal as the current collector, the conductivity and specific surface area of the composite electrode are greatly improved. At the same time, the porous structure is conducive to the diffusion of SF6 gas, increases the reaction sites of SF6 gas and reduces the polarization effect of the reaction, so that sulfur hexafluoride and relay electrolyte can fully react, and the specific energy of the relay system is greatly improved.
[0023] 4. This invention uses LiNO3-DMAC / FEC as the electrolyte in the relay battery. The solvent DMAC, with its high DN value, can increase the discharge voltage of the fluorinated carbon material by reducing the bond energy of the carbon-fluorine bond. Simultaneously, it can also regulate the morphology of the generated lithium fluoride, thereby enhancing the activity of the carbon produced in the reaction and promoting the subsequent reaction of sulfur hexafluoride and FEC. Furthermore, the FEC in the solvent can act as a film-forming agent on the lithium metal surface to avoid side reactions and can also serve as an active material to further enhance the system's discharge specific energy. Attached Figure Description
[0024] Figure 1 An optical photograph of the relay battery obtained in Example 1.
[0025] Figure 2 The discharge curve of a relay battery assembled in 1M LiNO3-DMAC / FEC electrolyte using a highly conductive, high specific surface area fluorinated carbon composite electrode at 25℃ is shown.
[0026] Figure 3 The image shows the XRD pattern of the positive electrode after the relay battery has discharged.
[0027] Figure 4 This is a SEM image of metallic lithium after the relay battery has discharged.
[0028] Figure 5 This is a diagram illustrating the action mechanism of DMAC and FEC in a multifunctional electrolyte. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0030] The present invention discloses a method for preparing a relay-type lithium battery with solid-liquid-gas synergistic discharge, comprising the following steps:
[0031] Step 1: Add the dry powders of fluorinated carbon, nitrogen-doped mesoporous carbon, and sodium carboxymethyl cellulose (CMC) to the ball mill jar in sequence, wherein the mass percentage of CMC is 2% and the mass percentage of nitrogen-doped mesoporous carbon is not less than 15%, and mix the dry powders evenly using a ball mill.
[0032] Step 2: Add distilled water to the uniform dry powder obtained in Step 1 to adjust the solid content of the slurry to 15%-25%, and continue to mix the slurry using a ball mill; the percentages are by mass.
[0033] Step 3: Add a water-based binder to the slurry obtained in Step 2. The binder accounts for 4% of the mass of the slurry. Continue to mix the slurry using a ball mill.
[0034] Step 4: The slurry obtained in Step 3 is evenly coated onto the ultrathin foam metal and dried at 100-150℃ for 10-12 hours under -80kPa to obtain the positive electrode sheet of the relay battery.
[0035] Step 5: Assemble the positive electrode, lithium metal and electrolyte obtained in Step 4 into a relay battery.
[0036] In step one, the fluorinated carbon used has a fluorine-to-carbon ratio not exceeding 1.3 and a specific surface area greater than 50 m². 2 / g; nitrogen content of nitrogen-doped mesoporous carbon ≥0.2%, percentage is by mass, specific surface area ≥20m² 2 / g, the ball mill speed is 250-350r / min, and the ball milling time is 1-1.5h.
[0037] In step two, the ball mill rotates at 350-450 r / min, and the milling time is 10-12 h, resulting in a uniform fluid mixture.
[0038] In step three, the water-based binder is one of polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), and polyacrylic acid (PAA), the ball mill speed is 250-270 r / min, and the ball milling time is 10-15 min.
[0039] In step four, the ultrathin foam metal is one of foamed nickel, foamed aluminum, and foamed nickel-molybdenum.
[0040] In step five, the electrolyte is LiNO3-DMAC / FEC, the concentration of LiNO3 is 0.8-2M, and the volume ratio of FEC does not exceed 6%.
[0041] Preferably, in step one, the fluorinated carbon used has a fluorine-to-carbon ratio of no more than 1.3 and a specific surface area greater than 50 m². 2 / g; nitrogen content of nitrogen-doped mesoporous carbon ≥0.2%, percentage is by mass, specific surface area ≥20m² 2 / g, the ball mill speed is 250-350 r / min, and the ball milling time is 1-1.5 h; in step two, the ball mill speed is 350-450 r / min, and the ball milling time is 10-12 h, and the final mixture is a uniform fluid; in step three, the aqueous binder is one of polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), and polyacrylic acid (PAA), and the ball mill speed is 250-270 r / min, and the ball milling time is 10-15 min; in step four, the ultrathin foam metal is one of foamed nickel, foamed aluminum, and foamed nickel-molybdenum; in step five, the electrolyte is LiNO3-DMAC / FEC, the concentration of LiNO3 is 0.8-2 M, and the volume ratio of FEC does not exceed 6%.
[0042] The above-described preparation method yields a relay-type lithium battery with solid-liquid-gas synergistic discharge.
[0043] The following is combined Figures 1 to 5 The invention's content, features, and effects are described in detail below, with examples provided and accompanying drawings:
[0044] Example 1
[0045] Step 1: Add the dry powders of fluorinated carbon, nitrogen-doped mesoporous carbon, and CMC (sodium carboxymethyl cellulose) to the ball mill jar in sequence. The mass percentage of CMC is 2%, the mass percentage of nitrogen-doped mesoporous carbon is 15%, and the mass percentage of fluorinated carbon is 79%. Mix the dry powders evenly with a ball mill at a speed of 250 r / min for 1 hour.
[0046] Step 2: Add distilled water to the uniform dry powder obtained in Step 1 to adjust the solid content of the slurry to 15%. Continue to mix the slurry using a ball mill at a speed of 350 r / min for 10 h.
[0047] Step 3: Add water-based binder PTFE to the slurry obtained in Step 2. The binder accounts for 4% of the mass of the slurry. The ball mill speed is 250 r / min and the ball milling time is 10 min.
[0048] Step 4: The slurry obtained in Step 3 is uniformly coated onto ultrathin nickel foam, and then dried at 130°C for 10 hours under a vacuum of -90 kPa to finally obtain a fluorinated carbon composite electrode with high conductivity and high specific surface area.
[0049] Step 5: Assemble the positive electrode sheet, lithium metal and 0.8M LiNO3-DMAC / FEC (94:6) multifunctional electrolyte obtained in Step 4 into a relay battery.
[0050] Experimental results:
[0051] The image of the relay battery prepared in Example 1 is shown below. Figure 1 As shown.
[0052] Figure 1 The image shows a photograph of the relay battery prepared in Example 1. As can be seen from the image, the battery consists of a cell and an air bag.
[0053] The high-conductivity, high-specific-surface-area fluorinated carbon composite electrode prepared in Example 1 exhibits excellent electrochemical performance in a relay battery with solid-liquid-gas synergistic discharge. It displays three discharge voltage plateaus at a current density of 0.1 A / g, indicating the occurrence of the relay reaction between fluorinated carbon, sulfur hexafluoride, and the multifunctional electrolyte (e.g., Figure 2 (As shown).
[0054] Depend on Figure 2 The discharge curves of the relay battery exhibit three voltage plateaus, corresponding from high to low to the discharge reactions of fluorinated carbon, sulfur hexafluoride, and the multifunctional electrolyte, respectively. The discharge voltage plateau of fluorinated carbon reaches 2.8V, higher than the 2.6V discharge voltage in the traditional carbonate electrolyte. This is mainly due to the DMAC in the multifunctional electrolyte lowering the bond energy of the carbon-fluorine bond and regulating the morphology of lithium fluoride formation. The discharge voltage plateau of sulfur hexafluoride starts at 2.6V, higher than the 2.4V discharge voltage reported in the literature. This may be because the strong nucleophilicity of pyridine nitrogen and pyrrole nitrogen in the conductive agent lowers the reaction barrier of sulfur hexafluoride and enhances its adsorption of gases, while the porous electrode structure lowers the diffusion barrier of gases and lithium ions. The discharge voltage of the multifunctional electrolyte starts at 2V, indicating that the carbon in the discharge product of the fluorinated carbon composite electrode has good conductivity.
[0055] Figure 3 The image shows the XRD pattern of the positive electrode after the relay battery reaction. The XRD pattern reveals diffraction peaks at 37°, 45°, and 66° after discharge, corresponding to the formation of lithium fluoride. No corresponding diffraction peaks for lithium sulfide are observed in the pattern, possibly due to the low amount of lithium sulfide formed. This confirms the successful conduction of the relay reaction.
[0056] Figure 4 The image shows the SEM image of the negative electrode after the reaction of the relay battery. It can be seen from the image that the surface of the lithium metal is still relatively smooth after the reaction. This is mainly because lithium nitrate and FEC form an inorganic-rich SEI film on the surface of the lithium metal, which prevents the side reaction between DMAC and lithium metal.
[0057] Figure 5 This is a diagram illustrating the mechanism of action of a multifunctional electrolyte.
[0058] Example 2
[0059] Step 1: Add the dry powders of fluorinated carbon, nitrogen-doped mesoporous carbon, and CMC (sodium carboxymethyl cellulose) to the ball mill jar in sequence. The mass percentage of CMC is 2%, the mass percentage of nitrogen-doped mesoporous carbon is 20%, and the mass percentage of fluorinated carbon is 74%. Mix the dry powders evenly with a ball mill at a speed of 250 r / min for 1.5 h.
[0060] Step 2: Add distilled water to the uniform dry powder obtained in Step 1 to adjust the solid content of the slurry to 25%. Continue to mix the slurry using a ball mill at a speed of 450 r / min for 12 hours.
[0061] Step 3: Add water-based binder PTFE to the slurry obtained in Step 2. The binder accounts for 4% of the mass of the slurry. The ball mill speed is 270 r / min and the ball milling time is 15 min.
[0062] Step 4: The slurry obtained in Step 3 is uniformly coated onto ultrathin nickel foam, and then dried at 150°C for 12 hours under a vacuum of -90 kPa to finally obtain a fluorinated carbon composite electrode with high conductivity and high specific surface area.
[0063] Step 5: Assemble the positive electrode sheet, lithium metal and 2M LiNO3-DMAC / FEC (94:6) multifunctional electrolyte obtained in Step 4 into a relay battery.
[0064] Example 3
[0065] Step 1: Add the dry powders of fluorinated carbon, nitrogen-doped mesoporous carbon, and CMC (sodium carboxymethyl cellulose) to the ball mill jar in sequence. The mass percentage of CMC is 2%, the mass percentage of nitrogen-doped mesoporous carbon is 25%, and the mass percentage of fluorinated carbon is 69%. Mix the dry powders evenly with a ball mill at a speed of 200 r / min for 1.5 h.
[0066] Step 2: Add distilled water to the uniform dry powder obtained in Step 1 to adjust the solid content of the slurry to 20%. Continue to mix the slurry using a ball mill at a speed of 400 r / min for 11 hours.
[0067] Step 3: Add water-based binder PTFE to the slurry obtained in Step 2. The binder accounts for 4% of the mass of the slurry. The ball mill speed is 270 r / min and the ball milling time is 15 min.
[0068] Step 4: The slurry obtained in Step 3 is uniformly coated onto ultrathin nickel foam, and then dried at 100°C for 12 hours under a vacuum of -90 kPa to finally obtain a fluorinated carbon composite electrode with high conductivity and high specific surface area.
[0069] Step 5: Assemble the positive electrode sheet, lithium metal and 1.5M LiNO3-DMAC / FEC (94:6) multifunctional electrolyte obtained in Step 4 into a relay battery.
[0070] The above embodiments provide a detailed description of the present invention, but the content described is only a preferred embodiment of the present invention and should not be considered as limiting the scope of the present invention. All equivalent variations and improvements made within the scope of the present invention should fall within the patent coverage of the present invention.
Claims
1. A method for preparing a relay-type lithium battery with solid-liquid-gas synergistic discharge, characterized in that, Includes the following steps: Step 1: Add the dry powders of fluorinated carbon, nitrogen-doped mesoporous carbon, and sodium carboxymethyl cellulose (CMC) to the ball mill jar in sequence, wherein the mass percentage of CMC is 2% and the mass percentage of nitrogen-doped mesoporous carbon is not less than 15%, and mix the dry powders evenly using a ball mill. Step 2: Add distilled water to the uniform dry powder obtained in Step 1 to adjust the solid content of the slurry to 15%-25%, and continue to mix the slurry using a ball mill; the percentages are by mass. Step 3: Add a water-based binder to the slurry obtained in Step 2. The binder accounts for 4% of the mass of the slurry. Continue to mix the slurry using a ball mill. Step 4: The slurry obtained in Step 3 is evenly coated onto the ultrathin foam metal and dried at 100-150℃ for 10-12 hours under a vacuum of -90kPa to obtain the positive electrode sheet of the relay battery. Step 5: Assemble the positive electrode, lithium metal and electrolyte obtained in Step 4 into a relay battery; In step one, the fluorinated carbon used has a fluorine-to-carbon ratio not exceeding 1.3 and a specific surface area greater than 50 m². 2 / g; nitrogen content of nitrogen-doped mesoporous carbon ≥0.2% (mass percentage), specific surface area ≥20 m² 2 / g, the ball mill speed is 250-350 r / min, and the ball milling time is 1-1.5 h; in step two, the ball mill speed is 350-450 r / min, and the ball milling time is 10-12 h, and the final mixture is a uniform fluid; in step three, the aqueous binder is one of polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), and polyacrylic acid (PAA), and the ball mill speed is 250-270 r / min, and the ball milling time is 10-15 min; in step four, the ultrathin foam metal is one of foamed nickel, foamed aluminum, and foamed nickel-molybdenum; in step five, the electrolyte is LiNO3-DMAC / FEC, the concentration of LiNO3 is 0.8-2 M, and the volume ratio of FEC does not exceed 6%.
2. The relay-type lithium battery with solid-liquid-gas synergistic discharge prepared by the preparation method as described in claim 1.
Citation Information
Patent Citations
Preparation method of Ag@C-modified fluorinated carbon electrode material
CN109659515A
High-performance lithium carbon fluoride battery and preparation method thereof
CN112234202A
Carbon fluoride composite positive active material for lithium-carbon fluoride battery as well as preparation method and application of carbon fluoride composite positive active material
CN113299912A